Light and electrically responsive materials based on aligned carbon nanotubes. (September 2016) - Luo, Yongfeng; Yu, Xinghai
Graphical abstract: Highlights: Responsive composite materials of aligned carbon nanotubes are summarized. The composite materials exhibit rapid and reversible deformation. The composite materials exhibit rapid and reversible chromatic. Abstract: Responsive materials have been investigated for a lot of applications such as smart devices and sensors, which change shape, color, transparency, or functionality when stimulated by external stimuli. However, the practical applications of responsive materials have been largely hampered by their irreversible transitions under limited stimuli such as temperature, pH, and chemical. As a result, a lot of research has been paid to improve the reversibility of chromatism and deformation. In this review, the recent research of responsive materials based on aligned carbon nanotubes is described, with the focus on the responsive materials in response to light and electricity.